The relevance of early diagnosis of skin cancer in the middle-aged and elderly population: Scoping review (Research, Society and Development, 2024)
Objectives: To analyze prevention strategies for early skin cancer screening, as well as signs and symptoms that are often late, and to identify factors associated with the suggestion of skin neoplasia in middle-aged and elderly individuals. Methodology: Scoping Review, based on the procedures recommended by the Joanna Briggs Institute. The guiding question was established: "What is the relevance of early diagnosis of skin cancer in the middle-aged and elderly population and what are the nursing practices in the context of skin cancer prevention?". Searches will be carried out in three national and international databases on studies published between 2018 and 2023. Results: 1,443 studies were identified, of which 53 were duplicates and 1,189 were excluded. Based on the title and abstract, 201 studies were assessed and 35 studies were eligible for the full text reading stage. For this rapid scoping review, 8 studies were included. Discussion: The evidence found in the scope of this study showed that prevention campaigns are the main prevention strategies for the early detection of skin cancer. In addition to results showing age, family history, smoking and sun exposure as the main risk factors for developing the disease. Final considerations: The results of this study reaffirm the relevance of intensifying preventive actions in the context of health promotion, especially with regard to early diagnosis and public awareness, which should be constantly encouraged.